2017
DOI: 10.1210/en.2016-1848
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a Functional Kisspeptin/Kisspeptin Receptor System in Amphioxus With Implications for Origin of Neuroendocrine Regulation

Abstract: Amphioxus belongs to the Cephalochordata, which is the most basal subphylum of the chordates. Despite many studies on the endocrine system of amphioxus, key information about its regulation remains ambiguous. Here we clearly demonstrate the presence of a functional kisspeptin/kisspeptin receptor (Kiss-Kissr) system, which is involved in the regulation of reproduction in amphioxus. Evolutionary analyses revealed large expansion of Kiss and Kissr (gpr54) genes in amphioxus, and they might represent the ancestral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 61 publications
(40 reference statements)
0
21
0
Order By: Relevance
“…Furthermore, it was discovered recently that, as with vertebrate calcitonin receptor-like receptors (CLRs), functional expression of a B. floridae calcitonin-type receptor requires coexpression of receptor activity-modifying proteins (RAMPs) ( Sekiguchi et al, 2016 ). Kisspeptin-type signalling pathways have also been characterised in B. floridae , providing evidence of an evolutionary ancient role for kisspeptins in regulation of reproductive activity ( Wang et al, 2017 ).…”
Section: The Evolution and Diversity Of Neuropeptide Signalling Systementioning
confidence: 99%
“…Furthermore, it was discovered recently that, as with vertebrate calcitonin receptor-like receptors (CLRs), functional expression of a B. floridae calcitonin-type receptor requires coexpression of receptor activity-modifying proteins (RAMPs) ( Sekiguchi et al, 2016 ). Kisspeptin-type signalling pathways have also been characterised in B. floridae , providing evidence of an evolutionary ancient role for kisspeptins in regulation of reproductive activity ( Wang et al, 2017 ).…”
Section: The Evolution and Diversity Of Neuropeptide Signalling Systementioning
confidence: 99%
“…In the sea bass, Kp2(12), but not Kp1(15), can induce in vitro FSH release ( 73 ). Recently, it was reported that, in amphioxus ( Branchiostoma japonicum ), injection of amphioxus kisspeptin-like could upregulate the expression of gpb5 , a paralog of glycoprotein vertebrate-like β subunit ( 74 ). Our results on primary cultures of eel pituitary cells indicate that Kiss peptides may act directly at the pituitary cell levels in the eel.…”
Section: Discussionmentioning
confidence: 99%
“…In B. floridae, one of the reported genes encodes three putative peptides, suggesting additional intragene duplication of peptidic sequences, while the other genes encode a single peptide (492). More recently, 27 putative KissR-like genes were identified in B. floridae (856). Further expression and functional studies were performed in the amphioxus B. japonicum on one kiss-like gene (BjkissL-2) and one kissR-like gene (Bjgpr54L-1) (856).…”
Section: Kiss Before Vertebratesmentioning
confidence: 99%
“…More recently, 27 putative KissR-like genes were identified in B. floridae (856). Further expression and functional studies were performed in the amphioxus B. japonicum on one kiss-like gene (BjkissL-2) and one kissR-like gene (Bjgpr54L-1) (856). Using quantitative PCR and immunohistochemistry, the authors showed that BjkissL-2 mRNA and protein levels are higher in notochord/nerve cord, and especially in the anterior region of the nerve cord (cerebral vesicle) and Hatschek's pit (856).…”
Section: Kiss Before Vertebratesmentioning
confidence: 99%